Treatment of one-level degenerative lumbar spondylolisthesis with severe stenosis by oblique lateral interbody fusion: Clinical and radiological results after a minimal 1-year follow-up - Emeric Lefèvre (Interdisciplinary Neurosurgery, 2021)
Objective: To evaluate the clinical and radiological outcomes of patients undergoing one-level oblique lumbar interbody fusion (OLIF) combined with posterolateral fusion (PLF) with pedicle screws for the treatment of degenerative lumbar spondylolisthesis (DS) with a minimum follow-up of 1 year. Methods: A retrospective analysis of prospectively collected data was performed. Patients who underwent combined OLIF and PLF between March 2013 and December 2019 were considered for study eligibility. Patients were evaluated using the Oswestry Disability Index (ODI) and the Short Form-12 (SF-12) (physical PCS, mental MCS), self-evaluation of pain with a Visual Analog Scale (VAS) and walking distance. Compensation and sagittal balance were assessed using the Gille classification by full spine stereoradiography (EOS Imaging, Paris, France). Mechanical complications were also collected. Results: A total of 131 patients were included (mean (SD) age: 64.2 ± 10.4 years), and 127 patients were evaluated after a mean follow-up of 22 ± 12.3 months. The mean ODI at the last follow-up was 13.8 ± 12.9% (gain of 32.3 ± 15.5%; p < 0.0001), the mean PCS was 45.6 ± 7.7 (gain of 12.6 ± 9.8) and the mean MCS was 43.9 ± 11.9 (gain of 5.3 ± 13.5) (p < 0.0001). Ten patients (7.6%) had adjacent segment syndrome, and there was one vertebral body fracture. Patients with preoperative imbalance (SVA > 40 mm) had a significant improvement in SVA of 19.8 ± 32 mm (p = 0.025). Sagittal imbalance (Gille type 3) was not associated with a change in postoperative functional score (p = 0.52). Conclusions: OLIF improved functional scores at 1 year, with excellent outcomes in 80% of our patients with a low morbidity. Sagittal imbalance did not adversely affect the clinical outcomes. Level of evidence: 4 (cohort study).